The Language of Substance Use and Recovery: Novel Use of the Go/No–Go Association Task to Measure Implicit Bias. Issue 11 (19th September 2019) - Ashford, Robert D.; Brown, Austin M.; Curtis, Brenda
ABSTRACT: Previous research has found initial evidence that word choice impacts the perception and treatment of those with behavioral health disorders through explicit bias (i.e., stigma). A more robust picture of behavioral health disorder stigma should incorporate both explicit and implicit bias, rather than relying on only one form. The current study uses the Go/No–Go Association Task to calculate a d ′ (sensitivity) indexed score of automatic attitudes (i.e., implicit associations) to two terms, "addict" and "person with substance use disorder." Participants have significantly more negative automatic attitudes (i.e., implicit bias) toward the term "addict" in isolation as well as when compared to "person with a substance use disorder." Consistent with previous research on explicit bias, implicit bias does exist for terms commonly used in the behavioral health field. "Addict" should not be used in professional or lay settings. Additionally, these results constitute the second pilot study employed the Go/No–Go Association Task in this manner, suggesting it is a viable option for continued linguistic stigma related research.